2018
DOI: 10.2196/10046
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using a Smartwatch to Intensively Monitor Patients With Chronic Obstructive Pulmonary Disease: Prospective Cohort Study

Abstract: BackgroundAcute exacerbations of chronic obstructive pulmonary disease (COPD) are associated with accelerated decline in lung function, diminished quality of life, and higher mortality. Proactively monitoring patients for early signs of an exacerbation and treating them early could prevent these outcomes. The emergence of affordable wearable technology allows for nearly continuous monitoring of heart rate and physical activity as well as recording of audio which can detect features such as coughing. These sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 18 publications
(22 reference statements)
1
42
0
Order By: Relevance
“…We conducted a qualitative study to determine what patients with COPD would like to have in a wearable device and mobile application to help manage their condition. This study is part of a larger ongoing project to develop wearables for patients with COPD to improve self-management and detect acute exacerbations early [7, 8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a qualitative study to determine what patients with COPD would like to have in a wearable device and mobile application to help manage their condition. This study is part of a larger ongoing project to develop wearables for patients with COPD to improve self-management and detect acute exacerbations early [7, 8].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, we found that it was feasible for people with COPD to use wearables for real-time data collection, but many people were not interested in participating or did not complete the study. We found that patients with COPD wanted more from a wearable device [7].…”
Section: Introductionmentioning
confidence: 99%
“…oximeters and pedometers) and healthcare ‘apps’, has been identified as an innovative model to help optimise the provision of COPD care by supporting patients to enhance the knowledge and sense of control they possess over self-management practices such as self-monitoring and problem solving. 1214 Healthcare professionals (HCPs) can benefit from longitudinal datasets captured outside the clinic to inform decision-making and support self-management through the personalisation of treatment plans that are more aligned with patient needs and preferences. 1518…”
Section: Introductionmentioning
confidence: 99%
“…FitOn and Garmin which are mostly equipped with precision body sensors and have unique features to support healthy life by routinely tracking health activities such as body temperature, heart rate, oxygen saturation, respiratory health, physical activities, facial expression and voice recognition [4,5,[12][13][14][15]. Along with health tracking facilities, to support physical activities and to help in medical emergency; smart devices retain location tracking capabilities in collaborating with various service providers and popular social networks.…”
mentioning
confidence: 99%
“…Along with health tracking facilities, to support physical activities and to help in medical emergency; smart devices retain location tracking capabilities in collaborating with various service providers and popular social networks. With strong privacy features, these smart devices and radio signals may help in COVID-19 infection traceability, detection, smart isolation and may alert to an established centralized pandemic surveillance center for the traceability and detection of new and unidentified infected individuals or specific infested community by collecting individualized health data such as abnormal temperature, unrhythmic heart rates, abnormal oxygen saturation, respiratory distress, atypical voice pitch and unconscious facial recognition [2,8,[12][13][14][15]. Additionally, social network models plausible on real life social structures, activities, relations and comprises on everyday life activities for the wellbeing and socialization of mankind [3].…”
mentioning
confidence: 99%